1975
DOI: 10.1161/01.res.37.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in myocardial performance in the left ventricle of the dog.

Abstract: To determine whether significant regional differences in shortening exist in the canine left ventricle, the shortening characteristics of small segments of the circumferentially oriented hoop axis fibers and the more longitudinally oriented fibers near the epicardium were examined using pairs of ultrasound crystals placed at three levels of the left ventricular free wall in the open-chest dog. Mean control shortening of the hoop axis fibers near the apex of the left ventricle averaged 20% of the end-diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(62 citation statements)
references
References 32 publications
3
56
1
2
Order By: Relevance
“…In line with previous reports [21,22], our results emphasize the concept that considering the myocardium as a uniformly functioning tissue might be misleading. Consequently, each portion of the left ventricular wall might have metabolic and perfusion needs which are specific in magnitude [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous reports [21,22], our results emphasize the concept that considering the myocardium as a uniformly functioning tissue might be misleading. Consequently, each portion of the left ventricular wall might have metabolic and perfusion needs which are specific in magnitude [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…The variations that occur in the myocardium in metabolic rate (Griggs et al 1972, Dunn andGriggs 1975), oxygenation (Gamble et al 1974;Schubert et al 1978;Weiss and Sinha 1978), and myocardial fiber shortening (LeWinter et al 1975) have become generally recognized. Similarly, the spatial heterogeneity of regional myocardial blood flow has been clearly demonstrated with indicator dilution methods (Bassingthwaighte et al 1972;Rose and Goresky 1976;Roselli and Harris 1979) and with the microsphere technique (Yipintsoi et al 1973;Falsetti et al 1975;Marcus et al 1977;Sestier et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…These investigators, and Liedke et al (17), by using angiographic techniques, showed greater shortening at the apex compared with the base of the LV. With dimension gauges implanted at the midwall in the direction of the midwall myofibers, shortening was found to be greatest in the apex (ϳ20%) and less at the midwall and base of the ventricle (16). In the transplanted human heart, longitudinal shortening tended to be greater on the posterior wall and approximately equal to circumferential shortening at anterior locations (11).…”
Section: Regional End-systolic Strains and Effects Of Afterloadmentioning
confidence: 95%